Influence of human capital on employability of management graduates from San Marcos University - Cuba Rosales, Luis (2018)
The present correlational type research project aimed to solve the problem between human capital, understood as educational training, and the employability of graduates of the professional career of administration. In this line, human capital is understood as educational training, expressed in the number of degrees and training obtained, as well as work experience, expressed in years. While for employability is understood, the salary, the time it takes to get a job, a salary increase or a promotion.Also for the field work, surveys were used to gather information about the training received and the level of salary income, among others, that the graduates have. Thus, the observational design and the statistical analysis show evidence of the relationship between the indicators of both variables. Based on the results of impact, the University can make a large contribution to the employability of its graduates by offering programs that they urgently need.